2022
DOI: 10.1021/acsorginorgau.1c00052
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Gold(I) Catalysis via Weak Interactions: New Fine-Tunable Impy Ligands

Abstract: A series of modular ImPy−carbene−Au(I) complexes are synthesized and fully characterized both in the solid state and in solution. The presence of oligoaryl units (phenyl and thienyl rings) at the C5-position of the ImPy core (in close proximity to the gold center) imprints on the organometallic species fine-tunable and predictable catalytic properties. A marked accelerating effect was recorded in several [Au(I)]-catalyzed electrophilic activations of unsaturated hydrocarbons when a CF 3 -containing aromatic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Very recently, Monari, Bandini and coworkers reported that controlling the weak secondary interactions between gold center and the ancillary NHC ligand constitutes a viable and rational strategy to boost the activity of the corresponding cationic gold(I) species (Figure 11). [28] To this purpose, they developed a series of modular ImPyÀ Au(I) complexes, whose C5-position is functionalized by electronically-differentiated aryl and oligothienyl groups, whose complexes 27 a-e are selected examples. [29] As a first model, the dearomatization of 1,3-dimethylnaphth-2-ol with N-phenyl-N-tosyl allenamide was selected.…”
Section: Impy-gold(i) Catalysts With Weak Intramolecular Interactionsmentioning
confidence: 99%
“…Very recently, Monari, Bandini and coworkers reported that controlling the weak secondary interactions between gold center and the ancillary NHC ligand constitutes a viable and rational strategy to boost the activity of the corresponding cationic gold(I) species (Figure 11). [28] To this purpose, they developed a series of modular ImPyÀ Au(I) complexes, whose C5-position is functionalized by electronically-differentiated aryl and oligothienyl groups, whose complexes 27 a-e are selected examples. [29] As a first model, the dearomatization of 1,3-dimethylnaphth-2-ol with N-phenyl-N-tosyl allenamide was selected.…”
Section: Impy-gold(i) Catalysts With Weak Intramolecular Interactionsmentioning
confidence: 99%
“…Even when only considering gold catalysis [6], the ImPy framework has been used to great effect [7]. The motif has been used to introduce sterically demanding NHCs with secondary gold-ligand interactions [8][9][10], chiral environments [11][12][13] including those enabling secondary interactions with substrates for asymmetric catalysis [14], cooperative and bimetallic catalysis [7,15], and redox-enabling function for Au(I)/(III) cycles [16,17]. Such L-shaped ligands provide scope to influence the reactivity profile of their resulting metal complexes through steric shielding, direct stabilising interactions with the metal, or by proximal effects to reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…1d). 8 This peculiar catalytic activity was rationalized based on secondary interactions regarding the cationic alkenyl-[Au(I)]-type intermediates B. 9 These findings, combined with our recent interest towards [Au(I)] assisted synthesis of polycyclic fused indolyl cores, 10 prompted us to verify the efficiency of Cat1 in the model hydrocarboxylation reaction of 1a (Fig.…”
mentioning
confidence: 96%
“…The arene⋯Au distance, that has been already proved to qualitatively predict the catalytic activity of the Au complexes in electrophilic activation of π-systems, was investigated for Cat2 and Cat3 . 8 These two pre-catalysts with electron-rich functionalization displayed longer arene⋯Au vs. Cat6 contact (3.352 Å) and a shortening of the distance was observed for meta -substituted arenes vs. para -ones (3.623 Å vs. 3.566 Å). Furthermore, both –NMe 2 groups have a high degree of planarity, due to the conjugation with the phenyl ring (see ESI†).…”
mentioning
confidence: 99%
See 1 more Smart Citation